Punishment and Reward in Charitable Giving : An Experimental Study on Decision-Making and Social Norms - Jeřábek, Václav; Kotrba, Vojtěch; Ježek, Jan; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates how individuals respond to the charitable decisions of their peers in a controlled experimental setting. Participants observe others’ donation behaviour and income, and can choose to reward, punish, or do nothing, each at a personal cost. The study examines how factors such as income, fairness, and social norms influence these sanctioning behaviours. The findings reveal that most participants choose inaction, while donors are significantly more likely to reward other donors and punish non-donors. Higher-income individuals are punished more frequently, especially when they do not donate. Although donating reduces one’s earnings, this loss is often offset by the rewards received from peers. As a result, donors are not financially worse off and may additionally benefit from the utility gained through the act of giving itself. This research offers new insights into the asymmetry between reward and punishment and shows how social evaluation is shaped by both relative income and moral expectations. It contributes to the understanding of cooperation, fairness, and norm enforcement in economic interactions.
Vedoucí práce: Vojtěch Kotrba
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses